“I sang the reeds as no one sang before me...”: semantics of the swamp in the poetry of K. D. Balmont - Snezko, Julija (Literatūra, 2019)
The article considers the semantics of the swamp in the poetry of K. D. Balmont, whose image, in comparison with other natural images in his works, seems to be insufficiently studied. The work shows its special significance for the poet – it remains relevant throughout his whole artistic path and evolves, enriched with new meanings. This study shows that the semantics of the image of the swamp go beyond the early diabolic discourse (in the framework of which the swamp was analyzed by Hansen-Löve) in a significant group of poems, where the swamp is part of the native space and the habitat of folklore entities. The work concludes that the swamp, in the works of Balmont, is gradually freed from the negative connotations traditionally associated with it and turns from a god-forsaken place into a space where the cycle of life and death is carried out. It can be argued that the dominant in the image of the swamp in the poet’s works is the realm of the plants.